An Urban Perspective upon Moldavian Settlements. From Political Desideratum to Territorial Reality - ADRIAN COVĂSNIANU; LILIANA-ELENA COVĂSNIANU (Romanian Review of Regional Studies, 2014)
This research study focused on the current state of the urban space in the historical Moldavian Region from an urban legislative perspective. Since the 2003-2005 stage, the settlement system in North-East Romania has undergone severe transformation. Thus, some villages were raised to the rank of towns, without meeting the legally defined minimum conditions, in terms of quantitative and qualitative indicators. By using the GIS technique and basic statistics, it was possible to analyse the current network of urban settlements in Moldavia (21 cities and 33 towns) from the perspective of 16 urban indicators. The indicators ranged from demography, access to safe water, sewerage, central heating, number of beds in hospitals, number of doctors to education facility access, culture and sports, hotels, road access and wastewater treatment facilities. All of the 16 indicators were summed and a final urban coefficient was obtained. The results were interpreted and particularly pointed out in GIS environment. The conclusions emphasise that, after nearly a decade, none of the current towns meets the minimum conditions of being an urban settlement.